Translation Strategies Of English Idioms Into Indonesian In The Adventure Of The Speckled Band, A Sherlock Holmes Story By Sir Arthur Conan Doyle - Walliddaena, La Ucha Elliana; Imansyah, Imansyah (JUPE : Jurnal Pendidikan Mandala, 2025)
This research aimed to explore the translation strategies and identify the types of idioms found in the novel The Adventure of the Speckled Band: Sherlock Holmes by Sir Arthur Conan Doyle. The study was based on two main theories. Baker’s theory was applied to identify the translation strategies used, including using an idiom of similar meaning but dissimilar form, using an idiom of dissimilar meaning and form, translation by paraphrase, and translation by omission. Meanwhile, McCarthy and O’Dell’s theory was employed to categorize idioms into types such as similes, binomials, proverbs, euphemisms, clichés and fixed statements, and idioms from other languages. The research employed a descriptive qualitative method and was designed as library research. Data were collected through five steps: close reading, identification, note-taking, classification, and coding, in order to ensure the validity of the findings. The results revealed that fifty-eight idioms were identified in the novel. The most frequently used translation strategy was translation by omission, indicating that the translator often chose to exclude idiomatic expressions that might not transfer well into the target language. Furthermore, the most common types of idioms found in the novel were clichés and fixed statements, suggesting the frequent use of conventional expressions in the source text.